2020
DOI: 10.1063/5.0019872
|View full text |Cite
|
Sign up to set email alerts
|

Physical vapor deposition of a polyamorphic system: Triphenyl phosphite

Abstract: In situ AC nanocalorimetry and dielectric spectroscopy were used to analyze films of vapor-deposited triphenyl phosphite. The goal of this work was to investigate the properties of vapor-deposited glasses of this known polyamorphic system and to determine which liquid is formed when the glass is heated. We find that triphenyl phosphite forms a kinetically stable glass when prepared at substrate temperatures of 0.75–0.95Tg, where Tg is the glass transition temperature. Regardless of the substrate temperature ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…[42][43][44][45] According to the two-order-parameter model, 45 these amorphous phases have different structures, configurational entropy, and relaxation dynamics. [46][47][48][49][50][51][52][53] Hence, they might serve as ideal model systems to provide crucial information on these poorly understood problems if structural changes can be finely controlled in the same chemical composition.…”
Section: Articlementioning
confidence: 99%
“…[42][43][44][45] According to the two-order-parameter model, 45 these amorphous phases have different structures, configurational entropy, and relaxation dynamics. [46][47][48][49][50][51][52][53] Hence, they might serve as ideal model systems to provide crucial information on these poorly understood problems if structural changes can be finely controlled in the same chemical composition.…”
Section: Articlementioning
confidence: 99%
“…For example, at high pressures, high-and low-density supercooled water phases are interconvertible through a first-order phase transition (27,28). Recent studies have demonstrated that such polyamorphic states can also be accessed through PVD in hydrogen-bonding systems with polymorphic crystal states at depositions above the nominal Tg (29,30). However, these structure-specific transitions do not provide a general resolution for the Kauzmann crisis.…”
Section: Significancementioning
confidence: 99%